THE EFFECT OF GOLIMUMAB ON ARTERIAL STIFFNESS IN PATIENTS WITH RHEUMATOID ARTHRITIS - L. A. Knyazeva; L. I. Knyazeva; N. S. Meshcherina; I. I. Goryainov; M. A. Stepchenko; E. M. Khardikova (Научно-практическая ревматология, 2018)
Objective: to evaluate the effect of golimumab (GLM) on arterial stiffness in patients with different clinical and immunological subtypes of rheumatoid arthritis (RA).Material and methods. Examinations were made in 48 patients with RA meeting the 1987 ACR/2010 EULAR classification criteria. The investigators visualized carotid arteries with determination of local vessel wall stiffness and studied regional arterial stiffness with assessment of contour pulse wave analysis before and 52 weeks after initiation of therapy.Results and discussion. Young and middle-aged RA patients without any concomitant cardiovascular diseases were found to have subclinical great artery involvement that was characterized by increases in intima-media thickness (IMT) and stiffness index β of the common carotid artery (CCA); by rises in peripheral augmentation index (AIp), stiffness index (SI), and reflection index (RI), the intensity of a change in which was associated with high DAS28 and seropositivity for rheumatoid factor (RF) and/or anti-cyclic citrullinated peptide (antiCCP) antibodies. GLM treatment in patients with RA was accompanied by a statistically significant decrease in DAS28 and a reduction in CCA IMT and local (carotid) stiffness of the vascular bed. More significant correction of the investigated parameters was achieved in patients with the seronegative subtype of the disease; in this group of patients, CCA IMT decreased by 29% by the end of observation (p=0.01), CCA SI β reduced by an average of 28.7% (p=0.0001). At 52 weeks after GLM therapy initiation, contour pulse wave analysis indicated that this subgroup of patients was observed to have decreases in AIp, SI, and RI to the control level; in RA seropositive for RF and/or anti-CCP, they reduced by an average of 1.8 (p=0.0001), 1.2 (p=0.005) and 1.6 (p=0.001) times, respectively.Conclusion. Along with high anti-inflammatory activity, GLM therapy in patients with RA has a vasoprotective effect on the walls of large elastic-type vessels (decreases in CCA IMT and SI β, AIp, and SI) and small muscular-type arteries (a reduction in RI).